Answer:
i wish i could help
Explanation:
iwe have that
x + (2x + 40) + (3x – 50) = 15,002
Reorder the terms:
(x+2x+3x)+(40-50)=15,002
Combine like terms:
x+2x+3x=6x
40-50=-10
6x-10=15,002
adds +10 both sides
6x-10+10=15,002+10
Combine like terms:
-10+10=0
15,002+10=15,012
6x=15,012
we have that
x + (2x + 40) + (3x – 50) = 15,002
Reorder the terms:
(x+2x+3x)+(40-50)=15,002
Combine like terms:
x+2x+3x=6x
40-50=-10
6x-10=15,002
adds +10 both sides
6x-10+10=15,002+10
Combine like terms:
-10+10=0
15,002+10=15,012
6x=15,012
we have that
x + (2x + 40) + (3x – 50) = 15,002
Reorder the terms:
(x+2x+3x)+(40-50)=15,002
Combine like terms:
x+2x+3x=6x
40-50=-10
6x-10=15,002
adds +10 both sides
6x-10+10=15,002+10
Combine like terms:
-10+10=0
15,002+10=15,012
6x=15,012
we have that
x + (2x + 40) + (3x – 50) = 15,002
Reorder the terms:
(x+2x+3x)+(40-50)=15,002
Combine like terms:
x+2x+3x=6x
40-50=-10
6x-10=15,002
adds +10 both sides
6x-10+10=15,002+10
Combine like terms:
-10+10=0
15,002+10=15,012
6x=15,012